Apresentação da Edição Especial Nau Social Gestão Social & Amazônia: práticas, ações e reflexões - Fernandes Azerêdo, Raoni; Vasconcellos Sobrinho, Mário; Cardoso Cançado, Airton; Moura de Sousa Fadul, Yana; Pacífico Filho, Miguel (NAU Social, 2022)
Apresentação da Edição Especial Nau Social Gestão Social & Amazônia: práticas, ações e reflexões